991. Blockade of the PD-1/PD-L1 Immune Checkpoint Pathway Improves Mortality, Infection Severity, and Fungal Clearance in an Immunosuppressed Murine Model of Invasive Pulmonary Mucormycosis. (4th December 2021) - Wurster, Sebastian; Albert, Nathaniel D; Kontoyiannis, Dimitrios P
Abstract: Background: Emerging experimental evidence suggests that immune checkpoint inhibitors (ICIs) enhance antifungal immunity. In addition, there is anecdotal evidence of potential benefit of adjunct PD-1 pathway blockade in patients with intractable mucormycosis. However, proof-of-concept data in animal models are lacking. Therefore, we compared the efficacy of PD-1 and PD-L1 inhibition in an immunosuppressed murine model of invasive pulmonary mucormycosis (IPM). Methods: Female 8-9-week-old BALB/c mice were immunosuppressed with cyclophosphamide (150 mg/kg on days -4 and -1, 100 mg/kg on day +3) and cortisone acetate (300 mg/kg on day -1) and infected intranasally with 50, 000 Rhizopus arrhizus spores (clinical isolate Ra-749, day 0). On days 0, +2, +4, and +6, mice received intraperitoneal injections of 250 µg/kg PD-1 or PD-L1 blocking antibodies versus (vs.) 250 µg/kg of the corresponding isotype antibodies (all antibodies from Leinco Technologies). Survival was monitored for 7 days post-infection. Infection severity was scored using the murine sepsis score (MSS, 0 = healthy to 3 = moribund). Fungal burden in lung tissue was determined by an 18S quantitative PCR assay on day +7 or upon death. 20 mice per treatment were assessed in 2 independent experiments. Results: Control mice with IPM receiving either of the unspecific isotype antibodies developed severe infection (median MSS on day 7, 2.5-3.0) and had a high 7-day mortality (50-55%). Compared to the corresponding isotype control, PD-L1 inhibition provided a strong therapeutic benefit, significantly improving morbidity (median MSS = 1.0 vs. 2.5, p = 0.002), 7-day mortality (15% vs. 50%, p = 0.02), and fungal burden (3.6k vs. 27.2k spore equivalents/lung, p < 0.001). In contrast, blockade of-PD-1 modestly yet non-significantly reduced infection severity (median MSS = 2.1 vs. 3.0, p = 0.48), 7-day mortality (35% vs, 55%, p = 0.12), and fungal burden (5.6k vs. 40.7k spore equivalents/lung, p = 0.09) compared to isotype control. Conclusion: Even without concomitant antifungals, blockade of PD-L1 and to a lesser extent of PD-1 improved mortality, infection severity, and fungal clearance in immunosuppressed mice with IPM. Immune phenotyping studies are in progress to better understand the protective antifungal activity of ICIs in IPM. Disclosures: Dimitrios P. Kontoyiannis, MD, Astellas (Consultant)Cidara Therapeutics (Advisor or Review Panel member)Gilead Sciences (Consultant, Grant/Research Support, Other Financial or Material Support, Honoraria)